ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE, SPRINGATE, ZMIJWESKI, DAN GROVER PADA PT.ULTRAJAYA MILK INDUSTRY AND TRADING COMPANY TBK DARI TAHUN 2016-2019 - Rahmawati, Novia; Sansitika, Desy Ria; Azmi, Zul; Suryadi, Nanda; Sinaga, Annisa Nauli (Research in Accounting Journal (RAJ), 2021)
The purpose of this study is to determine, analyze, and predict the financial difficulties faced by PT. Ultrajaya Milk Industry and Trading Company Tbk which are listed on the Indonesia Stock Exchange for the 2016-2019 period using the Atman Z-Score, Springate, Zmijweski, and Grover methods. This study uses secondary data, namely the annual financial statements of PT.Ultrajaya Milk Industry and Trading Company Tbk for the 2016-2019 period, recorded using document technique records and analyzed using the Atman Z-Score, Springate, Zmijweski, and Grover methods. The final results of this study indicate that PT.Ultrajaya Milk does not experience Financial Distress, this is because the results of using these methods obtain numbers that exceed the standards set by the method.